2017
DOI: 10.1111/jace.15291
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stability of KNbO3, NaNbO3, and K0.5Na0.5NbO3 in aqueous medium

Abstract: In recent years, potassium sodium niobate (K0.5Na0.5NbO3, KNN) has become popular and promising among perovskite lead‐free piezoceramic systems. In this study, the chemical stability of KNN powders in aqueous medium was investigated as a function of pH, time, and powder surface area. To better understand the dissolution behavior of the complex KNN stoichiometry, subconstituents such as potassium niobate (KNbO3, KN) and sodium niobate (NaNbO3, NN) were investigated separately first. Results showed that all of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The SiPt substrates, mostly comprised of Si and platinum metal, are expected to be chemically inert in the cell culture medium and to not release ions during in vitro studies. For KNN, ion release assays have been performed on powders in several studies. , The release of K + and Na + is 1–2 orders of magnitude higher than that of Nb 5+ due to the lower ionic strength of these ions. For 0.5 wt % powder suspensions in distilled water at room temperature the K + /Na + release is 1–3 mmol L –1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SiPt substrates, mostly comprised of Si and platinum metal, are expected to be chemically inert in the cell culture medium and to not release ions during in vitro studies. For KNN, ion release assays have been performed on powders in several studies. , The release of K + and Na + is 1–2 orders of magnitude higher than that of Nb 5+ due to the lower ionic strength of these ions. For 0.5 wt % powder suspensions in distilled water at room temperature the K + /Na + release is 1–3 mmol L –1 .…”
Section: Discussionmentioning
confidence: 99%
“…For KNN, ion release assays have been performed on powders in several studies. , The release of K + and Na + is 1–2 orders of magnitude higher than that of Nb 5+ due to the lower ionic strength of these ions. For 0.5 wt % powder suspensions in distilled water at room temperature the K + /Na + release is 1–3 mmol L –1 . These values are not negligible, and studies have linked the release of ions from KNN powders to a reduction in the rate of proliferation. , Although all cations in KNN (including Ca 2+ and Ti 4+ in the doped KNN composition in this work) are nontoxic in small concentrations, ,, local concentrations of leached ions can be high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It was reported that the formation enthalpies for potassium niobate and sodium niobate, respectively, are −207 and −142 kJ/mol. 20 However, no in-depth study on the activation energies for nucleation and growth has been reported for KNN thin films grown using chemical solution deposition. Thus, this work studies activation energies for perovskite transformation, nucleation, and growth from a manganese doped KNN solution modified with acetylacetone as a chelating agent.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the formation enthalpies for potassium niobate and sodium niobate, respectively, are −207 and −142 kJ/mol 20 . However, no in‐depth study on the activation energies for nucleation and growth has been reported for KNN thin films grown using chemical solution deposition.…”
Section: Introductionmentioning
confidence: 99%